The African strategy towards terrorist organizations (Nigeria and Somalia as a model) - Rafal Ayad Saleh (Tikrit Journal For Political Science, 2025)
<!–StartFragment–> We know that Africa as a continent occupies an important position in the global oil map, as oil production is concentrated in the West African region, with Nigeria at the forefront, followed by Libya, and then Algeria, and therefore African terrorism poses a direct threat to the security and stability of African regions, but its danger is more evident in the inability of the authority and the army to know in advance about the time and place of its occurrence. Perhaps among the main factors that contributed to the high level of threat posed by African terrorism to national security is the fragility and political corruption that the Sahel and sub-Saharan region in general, the absence of development initiatives by governments, and the deepening of ethnic and tribal conflicts, which provides a fertile field for the activity of terrorist organizations and their striking at the stability and national security of the countries of the region.